Positive electrode material precursor, positive electrode material, preparation method and battery
By adding functional additives to the reaction base liquid, the aggregation problem of the precursor of the small-particle positive electrode material is solved, and the capacity and rate performance of the positive electrode material are significantly improved, ensuring the improvement of sintering uniformity and electrical performance.
Patent Information
- Application Number
- CN202411569178.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-18
AI Technical Summary
The precursor of small-particle positive electrode material has serious agglomeration problems during the preparation process, resulting in irregular morphology of the positive electrode material, affecting the sintering uniformity and electrical properties.
By adding specific functional additives to the reaction base liquid, the mutual repulsion between small particles is enhanced, the adsorption phenomenon is reduced, and twin particles are eliminated, the spherical and uniformity of the particles are improved, thereby improving agglomeration phenomenon.
The agglomeration phenomenon of small-particle precursors is significantly improved, the capacity and rate performance of the positive electrode material are improved, and the sintering uniformity and electrical performance of the positive electrode material are improved.
Smart Images

Figure CN119461516A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery materials, and in particular to a positive electrode material precursor, a positive electrode material, a preparation method and a battery. Background Art
[0002] In the current preparation technology of small particle precursors, small particle crystals show agglomerative growth, and particles with a particle size of D50≤2μm are severely agglomerated, resulting in irregular morphology of small particle precursors with a D50 of 1-6μm. The proportion of heterogeneous particles is relatively large, resulting in different diffusion rates of lithium elements during the sintering process of single crystal positive electrode materials, affecting the sintering uniformity and the performance of the positive electrode materials.
[0003] CN116534914A discloses a method for preparing highly dispersed ternary precursor seed crystals. The method reduces the crystal growth ability and prevents seed crystal agglomeration through low-temperature nucleation (35-45°C) and negative pressure process in the reactor. Although the method improves the dispersion of particles with D50≤2μm, the co-precipitation reaction conditions in the growth period are quite different from the nucleation process, which will cause the morphology of the precursor to be non-uniform, affecting the sintering uniformity and electrical properties of the positive electrode material.
[0004] CN111196613A discloses a method for preparing a high-sphericity ternary precursor seed and a method for preparing a high-sphericity ternary precursor using the seed. Solid microspheres that are insoluble in the reaction base liquid and have a particle size larger than the diameter of a microporous filter tube are added to the reaction base liquid, and the crystal nuclei and the solid microspheres collide and rub to achieve a dispersion effect. After the nucleation is completed, the slurry is separated by a microporous filter tube, which reduces the natural sedimentation time. However, for a precursor with fine primary particles, there is a risk of fine powder being produced during the collision and friction between the crystal nuclei and the solid microspheres, which affects the electrical properties of the positive electrode material.
[0005] Therefore, it is urgent to solve the agglomeration problem in the preparation process of small particle precursors, which is of great significance for improving the performance of positive electrode materials. Summary of the invention
[0006] Aiming at the problem that the existing positive electrode material precursors, especially small particle precursors, suffer from agglomeration growth of crystal particles during the preparation process, and the obtained precursor particles are seriously agglomerated, the present invention provides a positive electrode material precursor, positive electrode material, preparation method and battery.
[0007] In order to achieve the above object, the present invention provides a method for preparing a positive electrode material precursor in a first aspect, the method comprising:
[0008] (1) preparing a reaction base liquid by mixing raw materials including a first precipitant, a first complexing agent, an auxiliary agent and water;
[0009] (2) subjecting the metal salt solution, the second precipitant, the second complexing agent and the reaction base liquid to a coprecipitation reaction to obtain a positive electrode material precursor;
[0010] Wherein, the auxiliary agent is selected from at least one of A salt, B salt, C salt and D salt; the A salt is selected from at least one of sulfate, bisulfate and thiosulfate; the B salt is sulfonate; the C salt is selected from chloride and / or hypochlorite; the D salt is selected from carbonate and / or bicarbonate;
[0011] The D50 of the positive electrode material precursor is 1-6 μm.
[0012] The second aspect of the present invention provides a positive electrode material precursor prepared by the method described in the first aspect.
[0013] The third aspect of the present invention provides a positive electrode material, which is obtained by sintering the positive electrode material precursor described in the second aspect and a lithium source or a sodium source.
[0014] A fourth aspect of the present invention provides a battery comprising the positive electrode material described in the third aspect.
[0015] The method for preparing a positive electrode material precursor provided by the present invention achieves significant improvement in the particle agglomeration phenomenon in the preparation process of a small particle precursor by adding a specific functional additive to a reaction base liquid. The precursor prepared by the method is used to prepare a positive electrode material, which can significantly improve the capacity and rate performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:
[0017] Figure 1 This is a SEM image of the positive electrode material precursor prepared in Preparation Example 1 of the present invention.
[0018] Figure 2 This is a SEM image of the positive electrode material precursor prepared in Comparative Preparation Example 1 of the present invention.
[0019] Figure 3 This is a SEM image of the positive electrode material precursor prepared in Preparation Example 2 of the present invention.
[0020] Figure 4 This is a SEM image of the positive electrode material precursor prepared in Comparative Preparation Example 2 of the present invention.
[0021] Figure 5 This is a SEM image of the positive electrode material precursor prepared in Preparation Example 3 of the present invention.
[0022] Figure 6 This is a SEM image of the positive electrode material precursor prepared in Comparative Preparation Example 3 of the present invention. DETAILED DESCRIPTION
[0023] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0024] A first aspect of the present invention provides a method for preparing a positive electrode material precursor, the method comprising:
[0025] (1) preparing a reaction base liquid by mixing raw materials including a first precipitant, a first complexing agent, an auxiliary agent and water;
[0026] (2) subjecting the metal salt solution, the second precipitant, the second complexing agent and the reaction base liquid to a coprecipitation reaction to obtain a positive electrode material precursor;
[0027] Wherein, the auxiliary agent is selected from at least one of A salt, B salt, C salt and D salt; the A salt is selected from at least one of sulfate, bisulfate and thiosulfate; the B salt is sulfonate; the C salt is selected from chloride and / or hypochlorite; the D salt is selected from carbonate and / or bicarbonate;
[0028] The D50 of the positive electrode material precursor is 1-6 μm.
[0029] The inventors of the present invention have discovered in their research that in the preparation process of small-particle positive electrode material precursors (D50 is 1-6μm), adding specific functional additives to the reaction base liquid can enhance the mutual repulsion between small-particle crystals (mainly by increasing the absolute value of the surface potential and improving the electrostatic repulsion between particles). Through the steric effect of the additives adsorbed on the surface of the particle crystals, a strong steric repulsion force is generated between the particles, reducing the occurrence of adsorption. At the same time, the additives can effectively eliminate twin particles, improve the sphericity and uniformity of the secondary particles, thereby significantly improving the agglomeration phenomenon of the obtained small-particle precursor.
[0030] According to the present invention, in the method for preparing the positive electrode material precursor, the particle size (D50) of the positive electrode material precursor is measured by a laser particle size analyzer.
[0031] According to the present invention, in the method for preparing the cathode material precursor, preferably, the A salt is selected from at least one of sodium sulfate, ammonium sulfate, ammonium hydrogen sulfate and sodium thiosulfate. Further preferably, the A salt is sodium sulfate.
[0032] According to the present invention, in the method for preparing the positive electrode material precursor, preferably, the B salt is sodium sulfonate.
[0033] According to the present invention, in the method for preparing the cathode material precursor, preferably, the C salt is selected from at least one of sodium chloride, ammonium chloride and sodium hypochlorite. Further preferably, the C salt is sodium chloride.
[0034] According to the present invention, in the method for preparing the positive electrode material precursor, preferably, the D salt is selected from sodium carbonate, sodium bicarbonate, ammonium carbonate and ammonium bicarbonate. Further preferably, the D salt is sodium carbonate.
[0035] According to a preferred embodiment of the present invention, the auxiliary agent is selected from salt A and / or salt B. The inventors of the present invention have found that when the auxiliary agent is salt A and / or salt B, the agglomeration phenomenon of the obtained small particle precursor can be better improved compared with the case where the auxiliary agent is salt C and / or salt D.
[0036] According to the present invention, in the method for preparing the positive electrode material precursor, the first precipitant and the second precipitant are relatively broad and can be selected conventionally in the art. Preferably, the first precipitant and the second precipitant are each independently selected from at least one of sodium hydroxide, sodium carbonate and sodium bicarbonate, and more preferably sodium hydroxide.
[0037] According to the present invention, in the method for preparing the positive electrode material precursor, the materials of the first precipitant and the second precipitant may be the same or different, and preferably they are the same.
[0038] Preferably, the first precipitant and the second precipitant are both sodium hydroxide.
[0039] According to the present invention, in the method for preparing the positive electrode material precursor, the restriction on the complexing agent is relatively broad, and conventional selections in the art can be adopted. Preferably, the first complexing agent and the second complexing agent are ammonia water.
[0040] According to the present invention, in the preparation method of the positive electrode material precursor, the metal salt in the metal salt solution may include a first metal salt and a second metal salt; wherein the first metal salt is a nickel salt, and the second metal salt is selected from a manganese salt and / or a salt containing element M; wherein the element M may be selected from at least one of Co, Al, Fe, Zn, Cr, Ti and Mg.
[0041] In the present invention, for the metal salt in the metal salt solution, the molar ratio of the first metal salt calculated as element Ni: the second metal salt calculated as element Mn and / or element M is (25-98): (1-80). In the above ratio, when the second metal salt is entirely manganese salt, the amount of the second metal salt is calculated as the amount of element Mn; when the second metal salt is entirely salt containing element M, the amount of the second metal salt is calculated as the amount of element M; when the second metal salt includes both manganese salt and salt containing element M, the amount of the second metal salt is calculated as the sum of the amounts of element Mn and element M.
[0042] According to the present invention, the metal salt in the metal salt solution may be at least one of sulfate, carbonate, oxalate, acetate and chloride, preferably sulfate.
[0043] According to the present invention, in the method for preparing the cathode material precursor, the metal salt solution is an aqueous solution of the above-mentioned metal salt.
[0044] According to the present invention, in the method for preparing the positive electrode material precursor, in step (1), there is no particular limitation on the order of feeding the raw materials, as long as the raw materials can be fully mixed to obtain a uniform and stable reaction base liquid. According to a preferred embodiment of the present invention, the reaction base liquid can be prepared in the following manner:
[0045] The auxiliary agent, the first precipitant and the first complexing agent are sequentially added to water, and the mixture is fully stirred and mixed to obtain a uniform and stable reaction base liquid.
[0046] According to the present invention, in the method for preparing the positive electrode material precursor, in step (1), preferably, the amount of the first precipitant added is such that the pH value of the reaction base solution is 10-13.
[0047] According to the present invention, in the method for preparing the positive electrode material precursor, in step (1), preferably, the amount of the first complexing agent added is such that, in the reaction base solution, the concentration of the first complexing agent (in terms of NH 3 The total amount is 1-12g / L.
[0048] According to the present invention, in the method for preparing the positive electrode material precursor, in step (1), preferably, the amount of the auxiliary agent added is such that the concentration of the auxiliary agent (in terms of salt) in the reaction base solution is 0.01-0.15 g / L.
[0049] According to the present invention, in the method for preparing the positive electrode material precursor, in step (1), preferably, the volume of the reaction base liquid accounts for 50-80% of the volume of the reaction kettle used for the coprecipitation reaction.
[0050] According to the present invention, in the method for preparing the positive electrode material precursor, in step (2), preferably, the metal salt solution, the second precipitant and the second complexing agent are continuously introduced into the reaction base liquid prepared in step (1), and the feed flow rate is adjusted according to the requirements of the reaction conditions to carry out the co-precipitation reaction.
[0051] According to the present invention, in the preparation method of the positive electrode material precursor, in step (2), preferably, the conditions of the coprecipitation reaction include: the temperature of the reaction system is 40-80°C, the pH value of the reaction system is 10-13, and the concentration of the complexing agent in the reaction system is 1-12g / L. Wherein, the concentration of the complexing agent in the reaction system refers to the total concentration of the first complexing agent (from the reaction base liquid) present in the reaction system and the second complexing agent added in step (2).
[0052] According to the present invention, preferably, the coprecipitation reaction is carried out under a protective atmosphere, such as a nitrogen atmosphere, a helium atmosphere, a neon atmosphere, an argon atmosphere, and the like.
[0053] According to the present invention, in the method for preparing the positive electrode material precursor, in step (2), preferably, the concentration of the metal salt (based on the total molar concentration of metal cations) in the metal salt solution is 1-3 mol / L. During the coprecipitation reaction, preferably, the volume flow rate of the metal salt solution per hour is 1-10% of the volume of the reactor used for the coprecipitation reaction.
[0054] According to the present invention, in the method for preparing the positive electrode material precursor, in step (2), preferably, the second precipitant and the second complexing agent are each fed in the form of an aqueous solution. Preferably, the concentration of the aqueous solution of the second precipitant is 5-11 mol / L; the concentration of the aqueous solution of the second complexing agent (when the second complexing agent is ammonia water, it refers to NH 3 The calculated concentration) is 6-10 mol / L.
[0055] According to the present invention, in the method for preparing the positive electrode material precursor, in step (2), the feed flow rate of the second precipitant is such that the pH value of the reaction system is maintained at 10-13; the feed flow rate of the second complexing agent is such that the concentration of the complexing agent in the reaction system is maintained at 1-12 g / L.
[0056] According to the present invention, in the method for preparing the positive electrode material precursor, in step (2), when it is measured that the solid phase particles formed by the coprecipitation reaction reach the target particle size, the feeding is stopped and the preparation is ended, and then the product system is post-treated to obtain a positive electrode material precursor product.
[0057] In the present invention, the post-treatment includes washing, drying and screening in sequence.
[0058] By adopting the preparation method of the present invention, by adding a specific functional additive to the reaction base liquid, the particle agglomeration phenomenon in the preparation process of small particle precursors can be significantly improved. The positive electrode material precursor prepared by this method can be used to prepare positive electrode materials. Compared with the positive electrode material precursor prepared by the conventional method, the positive electrode material can have a higher capacity and better rate performance.
[0059] The second aspect of the present invention provides a positive electrode material precursor prepared by the method described in the first aspect.
[0060] The cathode material precursor provided by the present invention has a D50 of 1-6 μm, and is a small particle precursor in terms of particle size, with no adhesion or agglomeration between particles. The cathode material prepared by the precursor can have the performance advantages of high capacity and good rate performance.
[0061] According to the present invention, preferably, the chemical composition of the positive electrode material precursor satisfies the chemical formula (Ni x Mn y M z )(OH) 2 , wherein 0.25≤x≤0.98, 0≤y≤0.80, 0≤z≤0.80, y and z are not 0 at the same time, and x+y+z=1; the element M is selected from at least one of Co, Al, Fe, Zn, Cr, Ti and Mg.
[0062] The third aspect of the present invention provides a positive electrode material, which is obtained by sintering the positive electrode material precursor described in the second aspect and a lithium source or a sodium source.
[0063] According to the present invention, the positive electrode material for a lithium-ion battery can be prepared by sintering the positive electrode material precursor and a lithium source together.
[0064] In the present invention, the lithium source is broadly defined, and any lithium source that can be used to prepare positive electrode materials for lithium-ion batteries can be selected, preferably lithium hydroxide and / or lithium carbonate.
[0065] In the present invention, when the positive electrode material precursor and the lithium source are sintered together, preferably, the molar ratio of the positive electrode material precursor: the lithium source is 1:(1.01-1.1).
[0066] In the present invention, when the cathode material precursor and the lithium source are sintered together, preferably, the sintering conditions include: a temperature of 500-950° C. and a time of 8-20 h.
[0067] According to the present invention, a sodium ion battery positive electrode material can be prepared by sintering the positive electrode material precursor and a sodium source together.
[0068] In the present invention, the sodium source is broadly defined, and any lithium source that can be used to prepare positive electrode materials for sodium ion batteries can be selected, preferably sodium carbonate.
[0069] In the present invention, when the cathode material precursor and the sodium source are sintered together, preferably, the molar ratio of the cathode material precursor: the sodium source is 1:(1.01-1.25).
[0070] In the present invention, when the positive electrode material precursor is sintered together with the sodium source, preferably, the sintering adopts a two-stage sintering, and the sintering conditions include: the temperature of the first stage sintering is 500-800°C and the time is 4-10h; the temperature of the second stage sintering is 800-1100°C and the time is 6-15h.
[0071] In the present invention, sintering is preferably performed in an oxygen or air atmosphere.
[0072] The positive electrode material provided by the present invention is prepared by sintering the positive electrode material precursor provided by the present invention and a lithium source or a sodium source together. The particles of the positive electrode material precursor are free of adhesion and agglomeration, which is conducive to the deintercalation of lithium ions or sodium ions. During the sintering process, the diffusion speeds of lithium ions or sodium ions are almost the same, the sintering uniformity is good, and the prepared positive electrode material has the performance advantages of high capacity and good rate performance.
[0073] A fourth aspect of the present invention provides a battery comprising the positive electrode material described in the third aspect.
[0074] The battery provided by the present invention adopts the positive electrode material provided by the present invention, so that the battery has the performance advantages of high capacity and good rate performance.
[0075] The present invention will be described in detail below by way of examples. In the following examples and comparative examples, unless otherwise specified, all are conventional methods; the reagents and materials, unless otherwise specified, can be obtained from commercial sources.
[0076] Preparation Example 1
[0077] (1) In a volume of 1m 3 In a reaction kettle, 600 L of pure water was first added, the temperature was raised to 60°C, and then sodium sulfate, NaOH aqueous solution and ammonia water were added in sequence, and the mixture was fully stirred to obtain a reaction bottom liquid;
[0078] The pH value of the reaction solution was 11.6, wherein the concentration of sodium sulfate was 0.05 g / L, and the concentration of ammonia (NH 3 The content of the reaction liquid is 1.8 g / L; the volume of the reaction bottom liquid accounts for 61% of the volume of the reactor;
[0079] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate, cobalt sulfate and manganese sulfate, wherein the molar ratio of Ni:Co:Mn is 60:10:30 and the total concentration of metal cations is 2 mol / L), a NaOH aqueous solution (concentration of 10 mol / L) and an ammonia solution (concentration of 8 mol / L) into the above-mentioned reactor, and carrying out a coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 60° C.), wherein the flow rate of the metal salt solution is 30 L / h, the pH value of the reaction system is maintained at 11.2-12.0, and the ammonia (in the form of NH 3 The content of 1.5-2.0 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 800 rpm;
[0080] When the particle size D50 of the solid phase material in the reactor is measured to reach 3.54 μm, the feeding is stopped, and then washing, drying and sieving are carried out in sequence to obtain a positive electrode material precursor (denoted as P1).
[0081] The D50 of P1 is 3.54 μm, and the chemical composition satisfies the chemical formula (Ni 0.60 Co 0.10 Mn 0.30 )(OH) 2 .
[0082] The SEM test results of P1 are as follows: Figure 1 As shown, it can be seen that the P1 particles have no adhesion and no agglomeration.
[0083] Preparation Example 2
[0084] (1) In a volume of 1m 3 In a reaction kettle, 500 L of pure water was first added, the temperature was raised to 50° C., and then sodium thiosulfate, NaOH aqueous solution and ammonia water were added in sequence, and the mixture was fully stirred to obtain a reaction base liquid;
[0085] The pH value of the reaction solution was 12.5, wherein the concentration of sodium thiosulfate was 0.08 g / L, and the concentration of ammonia (NH 3 The content of the reaction liquid is 2.3 g / L; the volume of the reaction bottom liquid accounts for 51% of the volume of the reactor;
[0086] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate and cobalt sulfate, wherein the molar ratio of Ni:Co is 90:10 and the total concentration of metal cations is 1.5 mol / L), a NaOH aqueous solution (concentration of 10 mol / L) and an ammonia solution (concentration of 8 mol / L) into the above-mentioned reactor, and carrying out a coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 50° C.), wherein the flow rate of the metal salt solution is 20 L / h, the pH value of the reaction system is maintained at 12.0-13.0, and the ammonia (NH 3The content of 2-2.5 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 700 rpm;
[0087] When the particle size D50 of the solid phase material in the reactor is measured to reach 4.96 μm, the feeding is stopped, and then washing, drying and sieving are carried out in sequence to obtain a positive electrode material precursor (denoted as P2).
[0088] The D50 of P2 is 4.96 μm, and the chemical composition satisfies the chemical formula (Ni 0.90 Co 0.10 )(OH) 2 .
[0089] The SEM test results of P2 are as follows: Figure 3 As shown, it can be seen that the P2 particles have no adhesion and no agglomeration.
[0090] Preparation Example 3
[0091] (1) In a volume of 1m 3 In a reaction kettle, first add 700 L of pure water, heat to 70° C., then add ammonium sulfate, NaOH aqueous solution and ammonia water in sequence, stir and mix thoroughly to obtain a reaction bottom liquid;
[0092] The pH value of the reaction solution was 10.5, wherein the concentration of ammonium sulfate was 0.1 g / L, and the concentration of ammonia (NH 3 The content of the reaction liquid is 6.3 g / L; the volume of the reaction bottom liquid accounts for 74% of the volume of the reactor;
[0093] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate, iron sulfate and manganese sulfate, wherein the molar ratio of Ni:Fe:Mn is 40:20:40 and the total concentration of metal cations is 1.0 mol / L), a NaOH aqueous solution (concentration of 11 mol / L) and an ammonia solution (concentration of 8 mol / L) into the above-mentioned reactor, and carrying out a coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 70° C.), wherein the flow rate of the metal salt solution is 15 L / h, the pH value of the reaction system is maintained at 10.0-11.0, and the ammonia (in the form of NH 3 The content of 2-nitrogen-1-nitrogen (calculated) was 6.0-6.5 g / L, the nitrogen flow rate was 500 L / h, and the stirring speed was 650 rpm;
[0094] When the particle size D50 of the solid phase material in the reactor is measured to reach 3.95 μm, the feeding is stopped, and then washing, drying and sieving are carried out in sequence to obtain a positive electrode material precursor (denoted as P3).
[0095] The D50 of P3 is 3.95μm, and the chemical composition satisfies the chemical formula (Ni 0.40 Fe 0.20 Mn 0.40 )(OH)2 .
[0096] The SEM test results of P3 are as follows: Figure 5 As shown, it can be seen that the P3 particles have no adhesion and no agglomeration.
[0097] Preparation Example 4
[0098] (1) In a volume of 1m 3 In a reaction kettle, first add 750L of pure water, heat to 80°C, then add sodium sulfonate, NaOH aqueous solution and ammonia water in sequence, stir and mix thoroughly to obtain a reaction bottom liquid;
[0099] The pH value of the reaction solution was 11.6, wherein the concentration of sodium sulfonate was 0.12 g / L, and the concentration of ammonia (NH 3 The content of the reaction liquid is 7.5 g / L; the volume of the reaction bottom liquid accounts for 78% of the volume of the reactor;
[0100] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate, iron sulfate and manganese sulfate, wherein the molar ratio of Ni:Fe:Mn is 33:34:33 and the total concentration of metal cations is 1.8 mol / L), a NaOH aqueous solution (concentration is 5 mol / L) and an ammonia solution (concentration is 8 mol / L) into the above reactor, and performing a coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 80° C.), wherein the flow rate of the metal salt solution is 10 L / h, the pH value of the reaction system is maintained at 11.0-12.0, and the ammonia (NH 3 The content of 2-nitrogen-1-nitrogen (calculated) was 7.0-8.0 g / L, the nitrogen flow rate was 500 L / h, and the stirring speed was 500 rpm;
[0101] When the particle size D50 of the solid phase material in the reactor is measured to reach 1.54 μm, the feeding is stopped, and then washing, drying and sieving are carried out in sequence to obtain a positive electrode material precursor (denoted as P4).
[0102] The D50 of P4 is 1.54μm, and the chemical composition satisfies the chemical formula (Ni 0.33 Fe 0.34 Mn 0.33 )(OH) 2 .
[0103] Preparation Example 5
[0104] (1) In a volume of 1m 3 In a reaction kettle, 600 L of pure water was first added, the temperature was raised to 40°C, and then ammonium hydrogen sulfate, NaOH aqueous solution and ammonia water were added in sequence, and the mixture was fully stirred to obtain a reaction bottom liquid;
[0105] The pH value of the reaction solution was 12.0, wherein the concentration of ammonium bisulfate was 0.01 g / L, and the ammonia content (in terms of NH 3 The volume of the reaction bottom liquid accounts for 63% of the volume of the reactor;
[0106] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate, cobalt sulfate and manganese sulfate, wherein the molar ratio of Ni:Co:Mn is 95:3:2 and the total concentration of metal cations is 1.2 mol / L), a NaOH aqueous solution (concentration is 6 mol / L) and an ammonia solution (concentration is 8 mol / L) into the above reactor, and performing a coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 40° C.), wherein the flow rate of the metal salt solution is 25 L / h, the pH value of the reaction system is maintained at 11.5-12.5, and the ammonia (NH 3 The content of 10.0-11.0 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 450 rpm;
[0107] When the particle size D50 of the solid phase material in the reactor is measured to reach 2.76 μm, the feeding is stopped, and then washing, drying and sieving are carried out in sequence to obtain a positive electrode material precursor (denoted as P5).
[0108] The D50 of P5 is 2.76μm, and the chemical composition satisfies the chemical formula (Ni 0.95 Co 0.03 Mn 0.02 )(OH) 2 .
[0109] Preparation Example 6
[0110] (1) In a volume of 1m 3 In a reaction kettle, 650 L of pure water was first added, the temperature was raised to 55° C., and then sodium sulfonate, NaOH aqueous solution and ammonia water were added in sequence, and the mixture was fully stirred to obtain a reaction bottom liquid;
[0111] The pH value of the reaction solution was 11.0, wherein the concentration of sodium sulfonate was 0.05 g / L, and the concentration of ammonia (NH 3 The content of the reaction liquid is 9.5 g / L; the volume of the reaction bottom liquid accounts for 68% of the volume of the reactor;
[0112] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate, iron sulfate and manganese sulfate, wherein the molar ratio of Ni:Fe:Mn is 50:30:20 and the total concentration of metal cations is 3.0 mol / L), a NaOH aqueous solution (concentration is 7 mol / L) and an ammonia solution (concentration is 8 mol / L) into the above reactor, and performing a coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 55° C.), wherein the flow rate of the metal salt solution is 20 L / h, the pH value of the reaction system is maintained at 10.5-11.5, and the ammonia (NH 3 The content of 2-nitrogen-1-nitrogen (calculated) was 9.0-10.0 g / L, the nitrogen flow rate was 500 L / h, and the stirring speed was 350 rpm;
[0113] When the particle size D50 of the solid phase material in the reactor is measured to reach 5.42 μm, the feeding is stopped, and then washing, drying and sieving are carried out in sequence to obtain a positive electrode material precursor (denoted as P6).
[0114] The D50 of P6 is 5.42μm, and the chemical composition satisfies the chemical formula (Ni 0.50 Fe 0.30 Mn 0.20 )(OH) 2 .
[0115] Preparation Example 7
[0116] (1) In a volume of 1m 3 In a reaction kettle, 600 L of pure water was first added, the temperature was raised to 65° C., and then sodium sulfonate, NaOH aqueous solution and ammonia water were added in sequence, and the mixture was fully stirred to obtain a reaction bottom liquid;
[0117] The pH value of the reaction solution was 12.0, wherein the concentration of sodium sulfonate was 0.15 g / L, and the concentration of ammonia (NH 3 The content of the reaction liquid is 11.5 g / L; the volume of the reaction bottom liquid accounts for 64% of the volume of the reactor;
[0118] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate, iron sulfate, manganese sulfate and zinc sulfate, wherein the molar ratio of Ni:Fe:Mn:Zn is 29:30:33:8 and the total concentration of metal cations is 2.5 mol / L), a NaOH aqueous solution (concentration is 9 mol / L) and an ammonia solution (concentration is 8 mol / L) into the above reactor, and performing a coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 65° C.), wherein the flow rate of the metal salt solution is 40 L / h, the pH value of the reaction system is maintained at 11.3-12.3, and the ammonia (in the form of NH 3 The content of 11.0-12.0 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 200 rpm;
[0119] When the particle size D50 of the solid phase material in the reactor was measured to reach 5.98 μm, the feeding was stopped, and then washing, drying and sieving were carried out in sequence to obtain a positive electrode material precursor (denoted as P7).
[0120] The D50 of P7 is 5.98μm, and the chemical composition satisfies the chemical formula (Ni 0.29 Fe 0.30 Mn 0.33 Zn 0.08 )(OH) 2 .
[0121] Preparation Example 8
[0122] (1) In a volume of 1m 3 In a reaction kettle, 600 L of pure water was first added, the temperature was raised to 65°C, and then sodium chloride, NaOH aqueous solution and ammonia water were added in sequence, and the mixture was fully stirred to obtain a reaction bottom liquid;
[0123] The pH value of the reaction solution was 12.0, wherein the concentration of sodium chloride was 0.15 g / L, and the concentration of ammonia (NH 3 The content of the reaction liquid is 11.5 g / L; the volume of the reaction bottom liquid accounts for 64% of the volume of the reactor;
[0124] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate, iron sulfate, manganese sulfate and zinc sulfate, wherein the molar ratio of Ni:Fe:Mn:Zn is 29:30:33:8 and the total concentration of metal cations is 2.5 mol / L), a NaOH aqueous solution (concentration is 9 mol / L) and an ammonia solution (concentration is 8 mol / L) into the above reactor, and performing a coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 65° C.), wherein the flow rate of the metal salt mixed solution is 40 L / h, the pH value of the reaction system is maintained at 11.3-12.3, and the ammonia (NH 3 The content of 11.0-12.0 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 200 rpm;
[0125] When the particle size D50 of the solid phase material in the reactor was measured to reach 5.90 μm, the feeding was stopped, and then washing, drying and sieving were carried out in sequence to obtain a positive electrode material precursor (denoted as P8).
[0126] The D50 of P8 is 5.90 μm, and the chemical composition satisfies the chemical formula (Ni 0.29 Fe 0.30 Mn 0.33 Zn 0.08 )(OH) 2 .
[0127] Preparation Example 9
[0128] (1) In a volume of 1m3 In a reaction kettle, 600 L of pure water was first added, the temperature was raised to 65°C, and then sodium carbonate, NaOH aqueous solution and ammonia water were added in sequence, and the mixture was fully stirred to obtain a reaction bottom liquid;
[0129] The pH value of the reaction solution was 12.0, wherein the concentration of sodium carbonate was 0.15 g / L, and the concentration of ammonia (NH 3 The content of the reaction liquid is 11.5 g / L; the volume of the reaction bottom liquid accounts for 64% of the volume of the reactor;
[0130] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate, iron sulfate, manganese sulfate and zinc sulfate, wherein the molar ratio of Ni:Fe:Mn:Zn is 29:30:33:8 and the total concentration of metal cations is 2.5 mol / L), a NaOH aqueous solution (concentration is 9 mol / L) and an ammonia solution (concentration is 8 mol / L) into the above reactor, and performing a coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 65° C.), wherein the flow rate of the metal salt solution is 40 L / h, the pH value of the reaction system is maintained at 11.3-12.3, and the ammonia (in the form of NH 3 The content of 11.0-12.0 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 200 rpm;
[0131] When the particle size D50 of the solid phase material in the reactor is measured to reach 5.95 μm, the feeding is stopped, and then washing, drying and sieving are carried out in sequence to obtain a positive electrode material precursor (denoted as P9).
[0132] The D50 of P9 is 5.95μm, and the chemical composition satisfies the chemical formula (Ni 0.29 Fe 0.30 Mn 0.33 Zn 0.08 )(OH) 2 .
[0133] Comparative Preparation Example 1
[0134] (1) In a volume of 1m 3 In a reaction kettle, 600 L of pure water was first added, the temperature was raised to 60°C, and then NaOH aqueous solution and ammonia water were added in sequence, and the mixture was fully stirred to obtain a reaction bottom liquid;
[0135] The pH value of the reaction solution was 11.6, wherein ammonia (NH 3 The content of the reaction liquid is 1.8 g / L; the volume of the reaction bottom liquid accounts for 61% of the volume of the reactor;
[0136] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate, cobalt sulfate and manganese sulfate, wherein the molar ratio of Ni:Co:Mn is 60:10:30 and the total concentration of metal cations is 2 mol / L), a NaOH aqueous solution (concentration of 10 mol / L) and an ammonia solution (concentration of 8 mol / L) into the above-mentioned reactor, and carrying out a coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 60° C.), wherein the flow rate of the metal salt solution is 30 L / h, the pH value of the reaction system is maintained at 11.2-12.0, and the ammonia (in the form of NH 3 The content of 1.5-2.0 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 800 rpm;
[0137] When the particle size D50 of the solid phase material in the reactor was measured to reach 3.62 μm, the feeding was stopped, and then washing, drying and sieving were carried out in sequence to obtain a positive electrode material precursor (denoted as DP1).
[0138] The D50 of DP1 is 3.62μm, and the chemical composition satisfies the chemical formula (Ni 0.60 Co 0.10 Mn 0.30 )(OH) 2 .
[0139] The DP1 was tested by scanning electron microscope, and the results are as follows: Figure 2 As shown, it can be seen that DP1 particles are adhered and agglomerated.
[0140] Comparative Preparation Example 2
[0141] (1) In a volume of 1m 3 In a reaction kettle, 500 L of pure water was first added, the temperature was raised to 50°C, and then NaOH aqueous solution and ammonia water were added in sequence, and the mixture was fully stirred to obtain a reaction bottom solution;
[0142] The pH value of the reaction solution was 12.5, wherein ammonia (NH 3 The volume of the reaction bottom liquid accounts for 51% of the volume of the reactor.
[0143] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate and cobalt sulfate, wherein the molar ratio of Ni:Co is 90:10 and the total concentration of metal cations is 1.5 mol / L), a NaOH aqueous solution (concentration of 10 mol / L) and an ammonia solution (concentration of 8 mol / L) into the above-mentioned reactor, and carrying out a coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 50° C.), wherein the flow rate of the metal salt solution is 20 L / h, the pH value of the reaction system is maintained at 12.0-13.0, and the ammonia (in the form of NH 3The content of 2-2.5 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 700 rpm;
[0144] When the particle size D50 of the solid phase material in the reactor is measured to reach 5.03 μm, the feeding is stopped, and then washing, drying and sieving are carried out in sequence to obtain a positive electrode material precursor (denoted as DP2).
[0145] The D50 of DP2 is 5.03 μm, and the chemical composition satisfies the chemical formula (Ni 0.90 Co 0.10 )(OH) 2 .
[0146] The DP2 was tested by scanning electron microscope, and the results are as follows: Figure 4 As shown, it can be seen that DP2 particles are adhered and agglomerated.
[0147] Comparative Preparation Example 3
[0148] (1) In a volume of 1m 3 In a reaction kettle, 700 L of pure water was first added, the temperature was raised to 70°C, and then NaOH aqueous solution and ammonia water were added in sequence, and the mixture was fully stirred to obtain a reaction bottom solution;
[0149] The pH value of the reaction solution was 10.5, wherein ammonia (NH 3 The content of the reaction liquid is 6.3 g / L; the volume of the reaction bottom liquid accounts for 74% of the volume of the reactor;
[0150] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate, iron sulfate and manganese sulfate, wherein the molar ratio of Ni:Fe:Mn is 40:20:40 and the total concentration of metal cations is 1.0 mol / L), a NaOH aqueous solution (concentration of 11 mol / L) and an ammonia solution (concentration of 8 mol / L) into the above reactor, and performing a coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 70° C.), wherein the flow rate of the metal salt mixed solution is 15 L / h, the pH value of the reaction system is maintained at 10.0-11.0, and the ammonia (NH 3 The content of 2-nitrogen-1-nitrogen (calculated) was 6.0-6.5 g / L, the nitrogen flow rate was 500 L / h, and the stirring speed was 650 rpm;
[0151] When the particle size D50 of the solid phase material in the reactor was measured to reach 3.92 μm, the feeding was stopped, and then washing, drying and sieving were carried out in sequence to obtain a positive electrode material precursor (denoted as DP3).
[0152] The D50 of DP3 is 3.92μm, and the chemical composition satisfies the chemical formula (Ni 0.40 Fe 0.20 Mn 0.40 )(OH)2 .
[0153] The DP3 was tested by scanning electron microscope, and the results are as follows: Figure 6 As shown, it can be seen that DP3 particles are adhered and agglomerated.
[0154] Example 1
[0155] Lithium carbonate and the positive electrode material precursor P1 are uniformly mixed at a molar ratio of Li: (Ni+Co+Mn) of 1.03:1, and the mixture is sintered at a sintering temperature of 800°C and a sintering time of 12 hours in an oxygen atmosphere to obtain a lithium-ion battery positive electrode material (denoted as L1) after sintering.
[0156] The chemical composition of L1 satisfies the chemical formula Li 1.03 Ni 0.60 Co 0.10 Mn 0.30 O 2 .
[0157] Example 2
[0158] Lithium hydroxide and the positive electrode material precursor P2 are uniformly mixed at a molar ratio of Li: (Ni+Co) of 1.01:1, and the mixture is sintered at a sintering temperature of 700°C and a sintering time of 16 hours to obtain a lithium-ion battery positive electrode material (denoted as L2).
[0159] The chemical composition of L2 satisfies the chemical formula Li 1.01 Ni 0.90 Co 0.10 O 2 .
[0160] Example 3
[0161] Sodium carbonate and the above-mentioned positive electrode material precursor P3 are uniformly mixed at a molar ratio of Na: (Ni+Fe+Mn) of 1.08:1, and the mixture is sintered. The first sintering temperature is 600°C and the sintering time is 8h. Then the temperature is raised to 1000°C for the second sintering for 9h. The sintering atmosphere is oxygen. After sintering, a sodium ion battery positive electrode material (denoted as L3) is obtained.
[0162] The chemical composition of L3 satisfies the chemical formula Na 1.08 Ni 0.40 Fe 0.20 Mn 0.40 O 2 .
[0163] Example 4
[0164] Sodium carbonate and the above-mentioned positive electrode material precursor P4 are uniformly mixed at a molar ratio of Na: (Ni+Fe+Mn) of 1.01:1, and the mixture is sintered. The first sintering temperature is 700°C and the sintering time is 8h. Then the temperature is raised to 1000°C for the second sintering for 10h. The sintering atmosphere is oxygen. After sintering, a sodium ion battery positive electrode material (denoted as L4) is obtained.
[0165] The chemical composition of L4 satisfies the chemical formula Na 1.01 Ni 0.33 Fe 0.34 Mn 0.33 O 2 .
[0166] Example 5
[0167] Lithium hydroxide and the positive electrode material precursor P5 are uniformly mixed at a molar ratio of Li: (Ni+Co+Mn) of 1.1:1, and the mixture is sintered at a sintering temperature of 700°C and a sintering time of 16 hours in an oxygen atmosphere to obtain a lithium-ion battery positive electrode material (denoted as L5).
[0168] The chemical composition of L5 satisfies the chemical formula Li 1.10 Ni 0.95 Co 0.03 Mn 0.02 O 2 .
[0169] Example 6
[0170] Sodium carbonate and the above-mentioned positive electrode material precursor P6 are uniformly mixed at a molar ratio of Na: (Ni+Fe+Mn) of 1.25:1, and the mixture is sintered. The first sintering temperature is 500°C and the sintering time is 10h. Then the temperature is raised to 900°C for the second sintering for 12h. The sintering atmosphere is oxygen. After sintering, a sodium ion battery positive electrode material (denoted as L6) is obtained.
[0171] The chemical composition of L6 satisfies the chemical formula Na 1.25 Ni 0.50 Fe 0.30 Mn 0.20 O 2 .
[0172] Example 7
[0173] Sodium carbonate and the above-mentioned positive electrode material precursor P7 are uniformly mixed at a molar ratio of Na: (Ni+Fe+Mn+Zn) of 1.1:1, and the mixture is sintered. The first sintering temperature is 700°C and the sintering time is 4 hours. Then the temperature is raised to 1100°C for the second sintering for 10 hours. The sintering atmosphere is oxygen. After sintering, a sodium ion battery positive electrode material (denoted as L7) is obtained.
[0174] The chemical composition of L7 satisfies the chemical formula Na 1.10 Ni 0.29 Fe 0.30 Mn 0.33 Zn 0.08 O 2 .
[0175] Example 8
[0176] Sodium carbonate and the above-mentioned positive electrode material precursor P8 are uniformly mixed at a molar ratio of Na: (Ni+Fe+Mn+Zn) of 1.1:1, and then the mixture is sintered. The first sintering temperature is 700°C and the sintering time is 4 hours. Then the temperature is raised to 1100°C for the second sintering for 10 hours. The sintering atmosphere is oxygen. After sintering, the sodium ion battery positive electrode material (denoted as L8) is obtained.
[0177] The chemical composition of L8 satisfies the chemical formula Na 1.10 Ni 0.29 Fe 0.30 Mn 0.33 Zn 0.08 O 2 .
[0178] Example 9
[0179] Sodium carbonate and the above-mentioned positive electrode material precursor P9 are uniformly mixed at a molar ratio of Na: (Ni+Fe+Mn+Zn) of 1.1:1, and then the mixture is sintered. The first sintering temperature is 700°C and the sintering time is 4 hours. Then the temperature is raised to 1100°C for the second sintering for 10 hours. The sintering atmosphere is oxygen. After sintering, a sodium ion battery positive electrode material (denoted as L9) is obtained.
[0180] The chemical composition of L9 satisfies the chemical formula Na 1.10 Ni 0.29 Fe 0.30 Mn 0.33 Zn 0.08 O 2 .
[0181] Comparative Example 1
[0182] Lithium carbonate and the positive electrode material precursor DP1 are uniformly mixed at a molar ratio of Li: (Ni+Co+Mn) of 1.03:1, and the mixture is sintered at a sintering temperature of 800°C and a sintering time of 12 hours in an oxygen atmosphere to obtain a lithium-ion battery positive electrode material (denoted as DL1) after sintering.
[0183] The chemical composition of DL1 satisfies the chemical formula Li 1.03 Ni 0.60 Co 0.10 Mn0.30 O 2 .
[0184] Comparative Example 2
[0185] Lithium hydroxide and the positive electrode material precursor DP2 are uniformly mixed at a molar ratio of Li: (Ni+Co) of 1.01:1, and the mixture is sintered at a sintering temperature of 700°C and a sintering time of 16 hours to obtain a lithium-ion battery positive electrode material (denoted as DL2).
[0186] The chemical composition of DL2 satisfies the chemical formula Li 1.01 Ni 0.90 Co 0.10 O 2 .
[0187] Comparative Example 3
[0188] Sodium carbonate and the above-mentioned positive electrode material precursor DP3 are uniformly mixed at a molar ratio of Na: (Ni+Fe+Mn) of 1.08:1, and the mixture is sintered. The first sintering temperature is 600°C and the sintering time is 8h. Then the temperature is raised to 1000°C for the second sintering for 9h. The sintering atmosphere is oxygen. After sintering, the sodium ion battery positive electrode material (denoted as DL3) is obtained.
[0189] The chemical composition of DL3 satisfies the chemical formula Na 1.08 Ni 0.40 Fe 0.20 Mn 0.40 O 2 .
[0190] Test Case
[0191] Assemble batteries using the above-mentioned positive electrode materials L1-L9 and DL1-DL3:
[0192] Positive electrode: The positive electrode material (L1-L9, DL1-DL3), conductive agent (Carbon ECP / Super P), binder (PVDF) and dispersant (NMP) are uniformly mixed (wherein the weight ratio of positive electrode material: conductive agent: binder: dispersant is 95:1:2:2) to obtain positive electrode slurry, and the positive electrode slurry is uniformly coated on a clean aluminum foil, and then baked and pressed to obtain a positive electrode sheet;
[0193] Negative electrode: The negative electrode material (graphite), conductive agent (Carbon ECP / Super P), binder (SBR), and thickener (CMC) are weighed in a weight ratio of 95:1:2:2, and mixed evenly in deionized water to obtain a negative electrode slurry, and the negative electrode slurry is evenly coated on a clean copper foil, and then baked and pressed to obtain a negative electrode sheet;
[0194] Diaphragm: Celgard PP2075 diaphragm (Celgard, USA);
[0195] Electrolyte: 1 mol / L LiPF 6 Solution or NaPF 6 Solution (wherein the solvent is EC, PC, EP, PP mixed in a weight ratio of 1:1:2:6) as the electrolyte (lithium-ion batteries use LiPF 6 Solution, sodium ion battery using NaPF 6 solution);
[0196] The positive electrode, negative electrode, separator and electrolyte were assembled in sequence to obtain lithium ion batteries or sodium ion batteries (respectively denoted as B1-B9 and DB1-DB3), and the discharge capacity and capacity retention rate were tested at 25°C, a voltage of 2.7-4.2V and a rate of 0.2-2.0C. The results are shown in Table 1.
[0197] Table 1
[0198]
[0199] As can be seen from Table 1, under the above test conditions, the lithium ion batteries B1-B2 corresponding to Examples 1-2 of the present invention have higher discharge capacity and capacity retention rate compared with the electrical performance of the lithium ion batteries DB1-DB2 corresponding to Comparative Examples 1-2; the sodium ion battery B3 corresponding to Example 3 of the present invention has higher electrical capacity and capacity retention rate compared with the electrical performance of the sodium ion battery DB3 corresponding to Comparative Example 3. This is because the positive electrode material precursor prepared by the method of the present invention has a regular morphology, no agglomeration, and a small proportion of heterogeneous particles. During the sintering process, the diffusion rate of lithium ions or sodium ions is close to the same, which makes it easy for lithium ions or sodium ions to be deintercalated, which is beneficial to the transmission of lithium ions or sodium ions, making the positive electrode material sintering uniform, thereby significantly improving the capacity and rate performance of the battery.
[0200] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a positive electrode material precursor, characterized in that: The method comprises: (1) preparing a reaction base liquid by mixing raw materials including a first precipitant, a first complexing agent, an auxiliary agent and water; (2) subjecting the metal salt solution, the second precipitant, the second complexing agent and the reaction base liquid to a coprecipitation reaction to obtain a positive electrode material precursor; Wherein, the auxiliary agent is selected from at least one of A salt, B salt, C salt and D salt; the A salt is selected from at least one of sulfate, bisulfate and thiosulfate; the B salt is sulfonate; the C salt is selected from chloride and / or hypochlorite; the D salt is selected from carbonate and / or bicarbonate; The D50 of the positive electrode material precursor is 1-6 μm.
2. The preparation method according to claim 1, wherein The A salt is selected from at least one of sodium sulfate, ammonium sulfate, ammonium bisulfate and sodium thiosulfate; And / or, the B salt is sodium sulfonate; And / or, the C salt is selected from at least one of sodium chloride, ammonium chloride and sodium hypochlorite; And / or, the D salt is selected from at least one of sodium carbonate, sodium bicarbonate, ammonium carbonate and ammonium bicarbonate.
3. The preparation method according to claim 1 or 2, wherein The auxiliary agent is selected from A salt and / or B salt.
4. The preparation method according to any one of claims 1 to 3, wherein The first precipitant and the second precipitant are each independently selected from at least one of sodium hydroxide, sodium carbonate and sodium bicarbonate; And / or, the first complexing agent and the second complexing agent are ammonia water; And / or, the metal salt in the metal salt solution includes a first metal salt and a second metal salt; wherein the first metal salt is a nickel salt, and the second metal salt is selected from a manganese salt and / or a salt containing element M; wherein element M is selected from at least one of Co, Al, Fe, Zn, Cr, Ti and Mg.
5. The preparation method according to any one of claims 1 to 4, wherein: In step (1), the amount of the first precipitant added is such that the pH value of the reaction bottom solution is 10-13; and / or, in the reaction base solution, the concentration of the first complexing agent is 1-12 g / L; And / or, in the reaction base solution, the concentration of the auxiliary agent is 0.01-0.15 g / L; And / or, the volume of the reaction base liquid accounts for 50-80% of the volume of the reaction kettle used for the coprecipitation reaction.
6. The preparation method according to any one of claims 1 to 5, wherein: In step (2), the conditions of the coprecipitation reaction include: a temperature of 40-80° C., a pH value of the reaction system of 10-13, and a concentration of the complexing agent in the reaction system of 1-12 g / L; and / or, the concentration of the metal salt in the metal salt solution is 1-3 mol / L, and the volume flow rate per hour is 1-10% of the volume of the reactor used for the coprecipitation reaction; And / or, the second precipitant and the second complexing agent are each fed in the form of an aqueous solution; wherein the concentration of the aqueous solution of the second precipitant is 5-11 mol / L; the concentration of the aqueous solution of the second complexing agent is 6-10 mol / L; And / or, the feeding flow rate of the second precipitant is such that the pH value of the reaction system is maintained at 10-13; the feeding flow rate of the second complexing agent is such that the concentration of the complexing agent in the reaction system is maintained at 1-12 g / L.
7. A cathode material precursor obtained by the method according to any one of claims 1 to 6.
8. A positive electrode material, characterized in that The positive electrode material is prepared by sintering the positive electrode material precursor according to claim 7 and a lithium source or a sodium source.
9. The positive electrode material according to claim 8, wherein When the positive electrode material precursor and the lithium source are sintered together, the molar ratio of the positive electrode material precursor: the lithium source is 1: (1.01-1.1); the sintering conditions include: a temperature of 500-950° C. and a time of 8-20 hours; And / or, when the positive electrode material precursor and the sodium source are sintered together, the molar ratio of the positive electrode material precursor: the sodium source is 1:(1.01-1.25); the sintering adopts a two-stage sintering, and the sintering conditions include: the temperature of the first stage sintering is 500-800°C, and the time is 4-10h; the temperature of the second stage sintering is 800-1100°C, and the time is 6-15h.
10. A battery comprising the positive electrode material according to claim 8 or 9.
Citation Information
Patent Citations
Preparation method of high-sphericity ternary precursor seed crystal and method for preparing high-sphericity ternary precursor by using seed crystal
CN111196613A